FROM "HEADHUNTING" TO "HEAD-GROWING" - Albina R. Shaidullina (Высшее образование в России)
The paper discusses a technology of continuous «included» search and selection of prospective students by representatives of the basic enterprises which favorably differs from foreign analogues, such as Headhunting, Assessment, since it is based not only on the identification and selection, but on the growing and assistance to students' self-determination through development of sustainable motivation and attitudes on a continuous self-education, self-determination, self-development, self-presentation in the labor market, which contributes significantly to increasing the competitiveness of university graduates.